HMICL and CD123 in combination with a CD45/CD34/CD117 backbone – a universal marker combination for the detection of minimal residual disease in acute myeloid leukaemia. (24th October 2013) - Roug, Anne S.; Larsen, Hanne Ø.; Nederby, Line; Just, Tom; Brown, Gordon; Nyvold, Charlotte G.; Ommen, Hans B.; Hokland, Peter
Summary Real‐time quantitative polymerase chain reaction (qPCR) has been extensively validated for the detection of minimal residual disease (MRD) in acute myeloid leukaemia (AML). Meanwhile, multicolour flow cytometry (MFC) has received less attention because the so‐called leukaemia‐associated immunophenotypes (LAIPs) are generally of lower sensitivity and specificity, and prone to change during therapy. To improve MRD assessment by MFC, we here evaluate the combination of human Myeloid Inhibitory C‐type Lectin (hMICL, also termed C‐type lectin domain family 12, member A, CLEC12A) and CD 123 (also termed interleukin‐3 receptor alpha, IL3RA) in combination with CD34 and CD117 (KIT), as an MRD assay in pre‐clinical and clinical testing in 69 AML patients. Spiking experiments revealed that the assay could detect MRD down to 10−4 in normal bone marrow with sensitivities equalling those of validated qPCR assays. Moreover, it provided at least one MFC MRD marker in 62/69 patients (90%). High levels of hMICL/CD123 LAIPs at the post‐induction time‐point were a strong prognostic marker for relapse in patients in haematological complete remission (P < 0·001). Finally, in post induction samples, hMICL/CD123 LAIPs were strongly correlated (r = 0·676, P = 0·0008) to applied qPCR targets. We conclude the hMICL/CD123‐based MFC assay is a promising MRD tool in AML.